Cooperative Learning Type of Student Team Achievement Division on Learning Outcomes Writing Explanation Texts of Hufs Korea Students - Sulaeman, Agus; Hoon, Kim Dong (STIBA IEC JAKARTA, 2024)
This research aims to determine the effect of using student team achievement division type cooperative learning on the ability to write explanatory texts in Intermediate class students at Hankuk University of Foreign Studies, Korea. The method used is a Quasi Experimental type experimental method using two classes, namely the experimental class which is given treatment in the form of a cooperative learning method of the student team achievement division type and the control class which is not given treatment as a comparison class. The data collection technique uses essay writing tests and questionnaires to determine student responses to the student team achievement division type cooperative method. To analyze the data using the t test with a significance level of 0.05. The research population was all Intermediate class students, totaling 60 students. After being given cooperative method treatment, student team achievement division type, students' ability to write explanatory text increased. It can be concluded that accepting H1 rejects H0, thus it can be said that there is an influence of the use of cooperative learning methods of the student team achievement division type on the ability to write explanatory texts in the intermediate department class of Malay-Indonesia Hankuk University of Foreign Studies Korea.